(untitled) (Third Sector Social Economic Review, 2017)
The aim of this research is to examine the knowledge, attitudes and behaviors of the employees of Nevşehir Agricultural Credit Cooperative on sustainable development and to differentiate them in terms of some demographic variables. The questionnaires were prepared for the participation of 62 employees in Nevsehir Agricultural Credit Cooperative and face to face interview technique. According to the findings obtained from the relationship test, the level of knowledge and attitude towards employees’ sustainable development and work level were not found to be cognitively significant. Only a statistically meaningful and positive relationship was found between the level of attitude of employees towards sustainable development and the level of behavior. According to the findings of the regression test conducted to examine the effect of employees ’attitudes towards sustainable development on the behavior of employees, it was determined that employees’ attitudes towards sustainable development were statistically significant. Finally, several hypotheses have been tested to examine the relationship between employees’ knowledge, attitudes and behavior toward sustainable development and some demographic variables. According to the findings, it was determined that the knowledge level of employees about sustainable development did not differ statistically according to age, marital status, gender, working position, education level, seniority variables. Moreover, it has been observed that the attitudes and attitudes of employees towards sustainable development differ significantly from those of demographic variables only in terms of working position, and this variation is in employees in managerial positions and civil servant positions.